Experience related impacts on jump performance of elite and collegiate basketball - Sarvestan, J.; Cheraghi, M.; Shirzad, E.; Svoboda, Z. (SportMont, 2019)
Force-Time (F-T) curve variables of the vertical jump are known as contributing factors in jumping height. Experience-related differences might also have impacts on kinetic and kinematic outputs of athletes` jump. The aim of this study was to investigate the correlation between F-T curve variables with jump height (JH) and observe the differences between elite and collegiate basketball players. With institutional ethics approval, 12 elites (24.3±5.9 years, 195.4±23.1 cm, 89.1±15.2 kg, 13.6±2.3 years` experience) and 12 collegiate (21.6±2.5 years, 183.2±6.1 cm, 75.3±9.5 kg, 9.1±1.8 years` experience) male basketball players participated in this study. Correlation between F-T variables -included time, force, velocity, power and modified reactive strength (MRSI) - in the eccentric and concentric phases and JH was studied. Outcomes portrayed that concentric Relative Peak Force (r=0.71), Relative Peak Power (r=0.83), Peak Velocity (r=0.99) and MRSI (r=0.71) in elite players, and concentric Relative Peak Force (r=0.79), Average Power (r=65), Relative Peak Power (r=0.81), Peak Velocity (r=0.98) and MRSI (r=0.83) in collegiate players were significantly correlated with JH. Absolute and relative measures of power and force are shown to have a vital role in jump performance of basketball players. MRSI, which is defined as an explosiveness measurement in athletes, could be accounted as of jump performance criteria. Focusing on selected factors described above in training programs could enhance athlete jump performance, particularly in basketball society.